Balance of Payments Manual. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1993)
The Manual presents concepts, definitions, classifications, and conventions for compilation of balance of payments and international investment position statistics. As the international standard, the Manual serves as a guide for IMF member countries that regularly report balance of payments data to the IMF.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet